Factors Influencing Student Achievement in High School: A Mixed-Methods Approach - Rusadi, Hennitha Laila Sari (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
Abstract This study investigates the multifaceted factors influencing student achievement in high school through a comprehensive mixed-methods approach. Integrating quantitative data analysis and qualitative insights, the research aims to deepen understanding of how socioeconomic status (SES), school environment, and individual characteristics interact to shape academic outcomes. Quantitative analyses of standardized test scores, GPAs, and school records reveal significant correlations between SES and academic performance, highlighting disparities influenced by economic resources and family support systems. Qualitative findings from interviews and focus groups underscore the impact of school environment factors such as class size and teacher quality and individual traits like motivation and mental health on student achievement. The study advances educational research by integrating diverse methodologies to provide a nuanced perspective on the contextual nuances and interactions influencing student success. Findings contribute actionable insights for educational practice and policy, advocating for targeted interventions to enhance educational equity, support socio-emotional well-being, and foster inclusive learning environments conducive to academic excellence for all students.